2007
DOI: 10.1016/s1726-4901(09)70295-3
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hepatic Nitric Oxide Synthases in Rats with Thioacetamide-induced Acute Liver Failure and Encephalopathy

Abstract: Upregulation of hepatic eNOS was observed in rats with TAA-induced fulminant hepatic failure and encephalopathy, which might play a regulatory role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 34 publications
1
8
1
Order By: Relevance
“…In the liver, both Kupffer cells and hepatocytes can increase NO production in response to different stimuli 43,44 . We have recently found that hepatic eNOS mRNA and protein expression are enhanced in rats with TAA‐induced hepatic injury and encephalopathy, suggesting evidence of hepatic NO modulation by eNOS; 45 however, the plasma concentrations of NO metabolites, nitrite/nitrate, are not statistically different among the experimental groups in the current study. It seems that simvastatin treatment for 5 days exerts its relevant effect on liver without changing circulating levels of NO metabolites.…”
Section: Discussioncontrasting
confidence: 67%
“…In the liver, both Kupffer cells and hepatocytes can increase NO production in response to different stimuli 43,44 . We have recently found that hepatic eNOS mRNA and protein expression are enhanced in rats with TAA‐induced hepatic injury and encephalopathy, suggesting evidence of hepatic NO modulation by eNOS; 45 however, the plasma concentrations of NO metabolites, nitrite/nitrate, are not statistically different among the experimental groups in the current study. It seems that simvastatin treatment for 5 days exerts its relevant effect on liver without changing circulating levels of NO metabolites.…”
Section: Discussioncontrasting
confidence: 67%
“…The widespread uses of TAA are unavoidably accompanied by its toxicity and a number of ecotoxic effects in environmental pollution can result from TAA manipulation and its consequent presence in waste waters. These aspects become increasingly important due to high degree of hepatic and neurotoxic injury, and carcinogenity, of TAA, which has been demonstrated under various experimental conditions [10][11][12][13][14][15][16][17]. Thus, in these circumstances the detection of thioacetamide in real time has become more and more important.…”
Section: Introductionmentioning
confidence: 99%
“…In the liver, both hepatocytes and Kupffer cells augmented nitric oxide production in response to protean stimuli 39 . We also found hepatic endothelial nitric oxide mRNA and protein expression were enhanced in TAA‐injected rats, implying evidence of hepatic nitric oxide modulation by endothelial nitric oxide 40 . Furthermore, gabexate mesylate reduced nitrite and nitrate formation and inhibited constitutive nitric oxide synthase in a cell‐free extract 41 .…”
Section: Discussionmentioning
confidence: 57%